The role of health‐related claims and health‐related symbols in consumer behaviour: Design and conceptual framework of the CLYMBOL project and initial results. Issue 1 (March 2015) - Hieke, S.; Kuljanic, N.; Wills, J. M.; Pravst, I.; Kaur, A.; Raats, M. M.; van Trijp, H. C. M.; Verbeke, W.; Grunert, K. G.
Abstract Health claims and symbols are potential aids to help consumers identify foods that are healthier options. However, little is known as to how health claims and symbols are used by consumers in real‐world shopping situations, thus making the science‐based formulation of new labelling policies and the evaluation of existing ones difficult. The objective of the European Union‐funded project Role of health‐related CLaims and sYMBOLs in consumer behaviour (CLYMBOL) is to determine how health‐related information provided through claims and symbols, in their context, can affect consumer understanding, purchase and consumption. To do this, a wide range of qualitative and quantitative consumer research methods are being used, including product sampling, sorting studies (i.e. how consumers categorise claims and symbols according to concepts such as familiarity and relevance), cross‐country surveys, eye‐tracking (i.e. what consumers look at and for how long), laboratory and in‐store experiments, structured interviews, as well as analysis of population panel data. EU Member States differ with regard to their history of use and regulation of health claims and symbols prior to the harmonisation of 2006. Findings to date indicate the need for more structured and harmonised research on the effects of health claims and symbols on consumer behaviour, particularly taking into account country‐wide differences and individual characteristics such as motivation and ability to process health‐related information. Based on the studies within CLYMBOL, implications and recommendations for stakeholders such as policymakers will be provided.